The red Vienna sourcebook - McFarland, Rob 1968-; Zechner, Ingo 1972-; Spitaler, Georg 1972- (Studies in German literature, linguistics, and culture, 2020)
An encyclopedic selection of original documents from the Austrian capital's pathbreaking, progressive interwar period, translated and with contextualizing introductions and commentaries